Facile fabrication of linezolid/strontium coated hydroxyapatite/graphene oxide nanocomposite for osteoporotic bone defect - Shuhui Wu; Yunxiao Lai; Xian Zheng; Yang Yang (Heliyon, 2024)
Hydroxyapatite (HAp) coatings currently have limited therapeutic applications because they lack anti-infection, osteoinductivity, and poor mechanical characteristics. On the titanium substrate, electrochemical deposition (ECD) was used to construct the strontium (Sr)-featuring hydroxyapatite (HAp)/graphene oxides (GO)/linezolid (LZ) nanomaterial coated with antibacterial and drug delivery properties. The newly fabricated nanomaterials were confirmed by X-ray diffraction analysis (XRD), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) analysis and morphological features were examined by scanning electron microscope (SEM) analysis. The results reveal multiple nucleation sites for SrHAp/GO/LZ composite coatings due to oxygen-comprising moieties on the 2D surface of GO. It was shown to be favorable for osteoblast proliferation and differentiation. The elastic modulus and hardness of LZ nanocomposite with SrHAp/GO/LZ coatings were increased by 67 % and 121 %, respectively. An initial 5 h burst of LZ release from the SrHAp/GO/LZ coating was followed by 14 h of gradual release, owing to LZ's physical and chemical adsorption. The SrHAp/GO/LZ coating effectively inhibited both S. epidermidis and S. aureus, and the inhibition lasted for three days, as demonstrated by the inhibition zone and colony count assays. When MG-63 cells are coated with SrHAp/GO/LZ composite coating, their adhesion, proliferation, and differentiation greatly improve when coated with pure titanium. A novel surface engineering nanomaterial for treating and preventing osteoporotic bone defects, SrHAp/GO/LZ, was shown to have high mechanical characteristics, superior antibacterial abilities, and osteoinductivity.